Prinsip Non-Diskriminasi terhadap KPU dalam Pemenuhan Hak Pilih Disabilitas pada Pilkada 2024 - Dede Al Mustaqim; Mustaqim, Dede Al Mustaqim (IAIN Metro, 2025)
This study examines the application of the Non-Discriminatiebeginsel principle by the General Elections Commission (KPU) in ensuring the voting rights of persons with disabilities during the 2024 Regional Elections (Pilkada) in Kerandon Village. Using a field research method through direct observation, the study found that despite efforts by the KPU—such as providing assistive tools and improving accessibility—significant barriers remain. These include physical access limitations for wheelchair users, complex administrative procedures, and inadequate, non-neutral assistance and information. To realize an inclusive and equitable election, improvements are needed in infrastructure, simplification of voting procedures, accessible public information, and impartial, rights-based assistance.